Cardiometabolic Risk Trajectory Among Older Americans: Findings From the Health and Retirement Study. (12th July 2021) - Wu, Qiao; Ailshire, Jennifer A; Kim, Jung Ki; Crimmins, Eileen M
Abstract: Background: Cardiometabolic risk (CMR) is a key indicator of physiological decline with age, but age-related declines in a nationally representative older US population have not been previously examined. Methods: We examined the trajectory of CMR over 8 years of aging, from 2006/2008 to 2014/2016, among 3528 people older than age 50 in the Health and Retirement Study. We used growth curve models to examine change in total CMR as well as in individual cardiometabolic biomarkers to understand how baseline differences and rates of change vary across sociodemographic characteristics, by smoking status, and medication use. Results: Total CMR did not change among respondents who survived over 8 years. Despite significant differences in CMR across demographic and education groups at baseline, the pace of change with age did not differ by these characteristics. Among individual biomarkers, risk levels of diastolic blood pressure, resting heart rate, and total cholesterol decreased over 8 years while glycosylated hemoglobin, waist circumference, and pulse pressure increased over that time. Both the statistical significance levels and the magnitudes of the reduction over time with age in diastolic blood pressure, resting heart rate, and total cholesterol in models adjusted for age, race/ethnicity, gender, smoking, and education were reduced after controlling for blood pressure and cholesterol medication. Conclusions: The relatively constant total CMR level over 8 years occurred because some indicators improved with age while some deteriorated in this period. Medication use contributed to the improvement in blood pressure, resting heart rate, and total cholesterol.